Parental perceptions and attitudes towards the inclusion of children with neurodevelopmental, physical and sensory disabilities - Kárpáti, Noémi Vivien; Miklósi, Mónika (Frontiers in Psychiatry, 2026)
ObjectiveParental knowledge and attitudes are key determinants of inclusive education and children’s social participation, yet little is known about how parents conceptualize different types of disabilities. This study explored patterns of perceived knowledge, ability to help, and attitudes toward structural and relational inclusion across multiple disability categories within a network-analytic framework.MethodA cross-sectional online survey was completed by 347 Hungarian parents. Respondents rated five domains (knowledge, perceived impact, ability to help, class inclusion, and friendship inclusion) and reported prior experiences for nine disability types (autism spectrum disorder, attention-deficit/hyperactivity disorder, anxiety disorders, intellectual disability, orthopedic impairment, visual impairment, hearing impairment, speech impairment, and Down syndrome). Network analyses (EBICglasso) were performed for six sufficiently represented conditions.ResultsOverall, parents expressed favorable attitudes toward inclusion but reported limited self-efficacy in helping children with disabilities. Across networks, friendship and class inclusion formed a robust positive cluster, and perceived knowledge was positively linked to helping capability, although the strength of this connection varied across conditions. In contrast, perceived impact displayed negative edges with helping and inclusion willingness, particularly for ADHD, intellectual disability, and speech impairment.ConclusionThe findings highlight a consistent triadic structure connecting knowledge, ability to help, and inclusion willingness, with contact and perceived impact shaping their balance differently by disability type. Interventions promoting guided contact and targeted knowledge-building may enhance both perceived competence and inclusive attitudes. Future studies should adopt longitudinal or experimental designs, employ multi-item measures, and test causal pathways linking parental experience, knowledge, and inclusion behavior.